Construction of an all-solid-state artificial Z-scheme system consisting of Bi2WO6/Au/CdS nanostructure for photocatalytic CO2 reduction into renewable hydrocarbon fuel - Wang, Meng; Han, Qiutong; Li, Liang; Tang, Lanqin; Li, Haijin; Zhou, Yong; Zou, Zhigang (Nanotechnology, 2017)
An all-solid-state Bi2WO6/Au/CdS Z-scheme system was constructed for the photocatalytic reduction of CO2 into methane in the presence of water vapor. This Z-scheme consists of ultrathin Bi2WO6 nanoplates and CdS nanoparticles as photocatalysts, and a Au nanoparticle as a solid electron mediator offering a high speed charge transfer channel and leading to more efficient spatial separation of electron-hole pairs. The photo-generated electrons from the conduction band (CB) of Bi2WO6 transfer to the Au, and then release to the valence band (VB) of CdS to recombine with the holes of CdS. It allows the electrons remaining in the CB of CdS and holes in the VB of Bi2WO6 to possess strong reduction and oxidation powers, respectively, leading the Bi2WO6/Au/CdS to exhibit high photocatalytic reduction of CO2, relative to bare Bi2WO6, Bi2WO6/Au, and Bi2WO6/CdS. The depressed hole density on CdS also enhances the stability of the CdS against photocorrosion.An all-solid-state Bi2WO6/Au/CdS Z-scheme system was constructed for the photocatalytic reduction of CO2 into methane in the presence of water vapor. This Z-scheme consists of ultrathin Bi2WO6 nanoplates and CdS nanoparticles as photocatalysts, and a Au nanoparticle as a solid electron mediator offering a high speed charge transfer channel and leading to more efficient spatial separation of electron-hole pairs. The photo-generated electrons from the conduction band (CB) of Bi2WO6 transfer to the Au, and then release to the valence band (VB) of CdS to recombine with the holes of CdS. It allows the electrons remaining in the CB of CdS and holes in the VB of Bi2WO6 to possess strong reduction and oxidation powers, respectively, leading the Bi2WO6/Au/CdS to exhibit high photocatalytic reduction of CO2, relative to bare Bi2WO6, Bi2WO6/Au, and Bi2WO6/CdS. The depressed hole density on CdS also enhances the stability of the CdS against photocorrosion.